Musical Activity and Well-being: A New Quantitative Measurement Instrument - Krause, A.; Davidson, J.; North, Adrian (University of California Press, 2018)
A relationship between participation in musical activity and well-being has frequently been observed in recent research reports. Of these, some propose various well-being-related correlates of musical participation, but the varying samples and foci leave researchers without a reasoned appraisal of these correlates or a data-driven categorization of them. To address this lacuna, the current research reviewed of existing literature, identifying 562 benefits of well-being benefits perceived to be associated with musical participation. These items were used as the basis for developing a new quantitative measure to evaluate the perceived benefits of well-being arising from music participation. Principal axis factor analysis of data using this new, 36-item measure identified five discrete dimensions: mood and coping, esteem and worth, socialization, cognition, and self-actualization. The development of this well-being measure addresses a gap in the research and provides a tool for future research concerning musical participation.